Heterogeneity of alleles encoding high‐ and low‐prevalence red blood cell antigens across Africa: useful data to facilitate transfusion in African patients. (29th August 2013) - Silvy, Monique; Beley, Sophie; Granier, Thomas; Ba, Alhassane; Chiaroni, Jacques; Bailly, Pascal
Summary: Ethnic variations in red blood cell (RBC) antigens can be a source of alloimmunization, especially in migrant populations. To improve transfusion safety in continental Africa and countries with African migrants, we performed RBC genotyping to determine allele frequencies coding for high‐ and low‐prevalence antigens. A total of 481 blood samples were collected in ethnic groups from West, Central and East Africa. Molecular typing was performed using a polymerase chain reaction – reverse sequence specific oligonucleotide method. Results demonstrated no DI*1, DI*3, YT*2, SC*2, LW*7, KN*2 alleles in any sample and the CO*2 allele was rare. The frequency of LU*1 was comparable to that of European‐Caucasians (2%) except in Biaka pygmies (8%). The frequency of CROM*−1 was high in Mbuti pygmies (13%). High frequency of KN*7 and KN*6 may reflect selection pressure in the countries investigated. Analysis of Dombrock allele patterns confirmed uneven distribution of the DO*1 and DO*2 alleles with high frequencies of DO*−4 and DO*−5 in all groups. Altogether, findings demonstrated extensive allele‐frequency heterogeneity across Africa and suggested that knowledge of patient ethnicity gives information about the high‐prevalence antigens that may be lacking. These data are medically useful to support transfusion care of African migrants living in countries where the majority of the population is from a different ethnical background.